Synchronous transmission protocol for exchanging real-time and non-real-time multimedia data in group communications. (26th May 2009) - Tojo, Takuya; Takizawa, Makoto
In group communications, multiple processes send packets to multiple processes while receiving packets from multiple processes in a group. Even if each sender process sends packets to a receiver process at a rate that the receiver process can receive, packets from multiple sender processes may come to the process at a so high rate that the receiver process cannot receive, i.e., multi-source buffer overrun. In this paper, we propose a novel Synchronous Transmission Procedure (STP) where multiple processes do not arbitrarily send, i.e., synchronously send packets to a common destination process to resolve the multi-source buffer overrun.